2011
DOI: 10.1155/2011/491276
|View full text |Cite
|
Sign up to set email alerts
|

Using the Motivated Strategies for Learning Questionnaire and the Strategy Inventory for Language Learning in Assessing Motivation and Learning Strategies of Generation 1.5 Korean Immigrant Students

Abstract: This study examined the potential of utilizing the Motivated Strategies for Learning Questionnaire (MSLQ) and the Strategy Inventory for Language Learning (SILL) as instruments in measuring Generation 1.5 students' motivation and their use of language learning strategies. The MSLQ was of particular interest because it contains both a basic motivation subscale as well as a motivation/language learning strategies subscale. Participants of this study were 104 Generation 1.5 Korean immigrant students who were memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
3
6
1
1
Order By: Relevance
“…After collecting data and analysing the results, findings shows that students who contribute and engage actively without expecting any external motivation, with the question-generation activity, are those with strong intrinsic motivation drive. To support the findings of this current study, many studies conducted has also clearly evidenced that one of the principal determinant of success in learning is motivational factor [1].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…After collecting data and analysing the results, findings shows that students who contribute and engage actively without expecting any external motivation, with the question-generation activity, are those with strong intrinsic motivation drive. To support the findings of this current study, many studies conducted has also clearly evidenced that one of the principal determinant of success in learning is motivational factor [1].…”
Section: Discussionsupporting
confidence: 85%
“…advantages of integrating technology in classroom primarily to enhance self-regulated and student-centred learning, studies also reported that technology alone are unable to ensure students' success in learning, especially when it comes to other factors that might influence the learning process. Previous research, especially on language learning, has clearly evidenced that one of the principal determinants of success in learning is motivational factor [1].…”
Section: Introductionmentioning
confidence: 99%
“…He found that "in spite of some inherent uniqueness, L2 learning is similar to other subjects in the school environment and the MSLQ has the potential to be applied to L2-related studies" (p. 259). Stoffa, Kush, and Heo (2011) reported similar findings. Furthermore, they tested the possible overlap between MSLQ and Strategy Inventory for Language Learning (SILL) (Oxford, 1990).…”
Section: Statement Of the Problemsupporting
confidence: 68%
“…It is unknown how this unique experience interplays with students' motivation. Stoffa et al (2011) examined the potential of utilizing the Motivated Strategies for Learning Questionnaire (MSLQ) in measuring students' motivation and their use of language learning strategies. The MSLQ was of particular interest because it contains both a basic motivation subscale as well as a motivation learning strategies subscale.…”
Section: Introductionmentioning
confidence: 99%